Mitigating Gharar in Sharia Capital Market Volatility: Governance, Regulation, and Technology: Mitigasi Gharar dalam Volatilitas Pasar Modal Syariah: Tata Kelola, Regulasi, dan Teknologi - Muhammadi, Ali Akbar Ruhullah; Gustanto, Edo Segara; Arfaizar, Januariansyah; Muhammadi, Ali Asghar Fadlullah (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2024)
Abstract: In Islamic economics, gharar refers to uncertainty or ambiguity in transactions, which is prohibited because it can harm investors and undermine market stability. This study analyzes the characteristics of gharar and the impact of market volatility on Sharia-compliant issuers in Islamic capital markets. Employing a mixed juridical-empirical-normative approach, this study assesses relevant regulatory frameworks designed to mitigate gharar, including the Indonesian Ulama Council (MUI) Fatwa No. 80/2011 and the Financial Services Authority (OJK) Regulation No. 15/POJK.04/2015. The empirical component involves the collection and analysis of market data, while the normative dimension explores Sharia principles to formulate risk mitigation strategies. The research reveals that speculative activities, which are common in capital markets, exacerbate gharar by triggering irrational price movements and increased volatility. Such conditions obscure the intrinsic value of stocks and increase uncertainty in investment decision-making among Sharia-compliant investors. The findings underscore the need for stricter regulatory measures to curb speculative behavior, such as restricting margin trading and prohibiting short selling, alongside strengthening corporate governance and transparency among Sharia-compliant issuers. The study’s scope is limited by its focus on Indonesia’s Islamic capital market; therefore, future research should incorporate comparative analyses of international Sharia markets and investigate the potential role of financial technology (fintech) in enhancing transparency, accountability, and efficiency within Islamic capital markets. Abstrak: Gharar dalam ekonomi Islam merujuk pada ketidakpastian atau ambiguitas dalam transaksi yang dilarang karena berpotensi merugikan investor dan mengganggu stabilitas pasar. Penelitian ini menganalisis karakteristik gharar serta dampak volatilitas pasar terhadap emiten yang berprinsip syariah di pasar modal Islam. Dengan menggunakan pendekatan campuran yuridis-empiris-normatif, penelitian ini menilai kerangka regulasi yang relevan dalam upaya memitigasi gharar, termasuk Fatwa Majelis Ulama Indonesia (MUI) No. 80/2011 dan Peraturan Otoritas Jasa Keuangan (OJK) No. 15/POJK.04/2015. Komponen empiris penelitian ini mencakup pengumpulan dan analisis data pasar, sedangkan dimensi normatifnya menelaah prinsip-prinsip syariah untuk merumuskan strategi mitigasi risiko. Hasil penelitian menunjukkan bahwa aktivitas spekulatif yang lazim terjadi di pasar modal memperparah gharar dengan memicu pergerakan harga yang tidak rasional serta meningkatkan volatilitas. Kondisi tersebut mengaburkan nilai intrinsik saham dan menambah ketidakpastian dalam pengambilan keputusan investasi bagi investor yang mematuhi prinsip syariah. Temuan ini menegaskan perlunya penguatan regulasi guna menekan perilaku spekulatif, antara lain dengan membatasi perdagangan margin dan melarang short selling, disertai peningkatan tata kelola perusahaan dan transparansi di antara emiten syariah. Ruang lingkup penelitian ini terbatas pada pasar modal syariah di Indonesia, sehingga penelitian selanjutnya disarankan untuk memasukkan analisis komparatif terhadap pasar syariah internasional serta mengkaji potensi peran teknologi finansial (fintech) dalam meningkatkan transparansi, akuntabilitas, dan efisiensi di pasar modal Islam.